Isolation of alesin as a product of secondary metabolism of kales plant Allium sativum - Abeer Al-Jomaily; Muzahem Al-Mallah (College of Education for Pure Sciences, 2007)
This study successed in isolating the secondary metabolic product named allicin . This compound was isolated from various callus cultures & garlic plants produced from seeds as well . The isolated material was identified using thin layer chromatography (T.L.C.) , UV Spectrophotometer & infra red techniques . The results revealed that a single compound was isolated from all alcoholic plant extracts . the unique compound isolated from all samples has the same flow - rate and possess identical chemical structure when matched with standard allicin. The finding that callus culture contains high level of allicin up to 200 mg I 1 Og fresh weight , while garlic cloves contain 20 mg I 1 Og fresh weight which is known to be rich with allicin. This study described the effect of different photoperiod including continuous light or continuous dark and culture medium type on the accumulation of allicin .The results confirmed that callus tissue grown on MS medium enhanced the allicin quantity that reached up to 200 mg I 1 Og fresh weight of callus incubated in continuous light for two weeks .